Features of hippocampal astrocytic domains and their spatial relation to excitatory and inhibitory neurons. Issue 10 (12th June 2021) - Refaeli, Ron; Doron, Adi; Benmelech‐Chovav, Aviya; Groysman, Maya; Kreisel, Tirzah; Loewenstein, Yonatan; Goshen, Inbal
Abstract: The mounting evidence for the involvement of astrocytes in neuronal circuits function and behavior stands in stark contrast to the lack of detailed anatomical description of these cells and the neurons in their domains. To fill this void, we imaged >30, 000 astrocytes in hippocampi made transparent by CLARITY, and determined the elaborate structure, distribution, and neuronal content of astrocytic domains. First, we characterized the spatial distribution of >19, 000 astrocytes across CA1 lamina, and analyzed the morphology of thousands of reconstructed domains. We then determined the excitatory somatic content of CA1 astrocytes, and measured the distance between inhibitory neuronal somata to the nearest astrocyte soma. We find that on average, there are almost 14 pyramidal neurons per domain in the CA1, increasing toward the pyramidal layer midline, compared to only five excitatory neurons per domain in the amygdala. Finally, we discovered that somatostatin neurons are found in close proximity to astrocytes, compared to parvalbumin and VIP inhibitory neurons. This work provides a comprehensive large‐scale quantitative foundation for studying neuron‐astrocyte interactions. MAIN POINTS: Large scale detection of 3D astrocytic domains following CLARITY. Different distributions of neuronal content in CA1 and BLA astrocytic domains. SST neurons are located in close proximity to neighboring astrocytes, relative to PV, and VIP neurons.